2015
DOI: 10.1038/ejhg.2015.213
|View full text |Cite
|
Sign up to set email alerts
|

A rare variant (c.863G>T) in exon 7 of SMN1 disrupts mRNA splicing and is responsible for spinal muscular atrophy

Abstract: Proximal spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder caused by deletion or mutation of SMN1 (survival motor neuron 1). SMN exon 7 splicing is regulated by a number of exonic and intronic regulatory sequences and the trans-factors that bind them. Variants located in or near these regulated regions should be evaluated to determine their effect on splicing. We identified the rare variant c.863G4T (r.835_*3del, p.Gly279Glufs*5) in exon 7 of SMN1 in three patients affected with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This variant influenced SMN1 pre-mRNA splicing by disrupting the exonic splicing enhancer that binds to Tra2b1. 20 The other variant, c.835-5 T>G, located in the intron 6 3 0 -splicing region, reached approximately 93.3% disruption of mRNA exon 7 inclusion. To determine the effects of the c.835-5 site on exon 7 splicing, we also constructed the other two base substitutions in the c.835-5 site (c.835-5 T>A and c.835-5 T>C).…”
Section: Influence Of Variants On Smn1 Mrna and Protein Levelsmentioning
confidence: 98%
See 1 more Smart Citation
“…This variant influenced SMN1 pre-mRNA splicing by disrupting the exonic splicing enhancer that binds to Tra2b1. 20 The other variant, c.835-5 T>G, located in the intron 6 3 0 -splicing region, reached approximately 93.3% disruption of mRNA exon 7 inclusion. To determine the effects of the c.835-5 site on exon 7 splicing, we also constructed the other two base substitutions in the c.835-5 site (c.835-5 T>A and c.835-5 T>C).…”
Section: Influence Of Variants On Smn1 Mrna and Protein Levelsmentioning
confidence: 98%
“…45e48 Our study found that this variant was located near the exonic splicing enhancer region of exon 7 and showed that it was involved in Tra2b1 binding. 20 The other is the novel variant c.835-5T>G, which is located near the 3 0 splice site of intron 6. Because the c.835-5 position was not in the 3 0 splice site conserved consensus region (Py-rich NCAG), we cannot be certain whether this variant affects exon 7 splicing.…”
Section: Influencing the Correct Splicing Of Smn1mentioning
confidence: 99%
“…Some of them can be deeply located in intronic sequences 15 and are thus not covered by WES. Hence, direct probing of splice isoforms by RNA-seq is important, and has led to the discovery of multiple splicing defects based on single gene studies: skipping of multiple exons (exon 45–55) 16 and creation of a new exon by a deep intronic variant in DMD 17 , intron retention in LMNA caused by a 5′ splice site variant 18 , and skipping of exon 7 in SMN1 caused by a variant in a splicing factor binding site 19 . Altogether, RNA-seq promises to be an important complementary tool to facilitate molecular diagnosis of rare genetic disorders.…”
mentioning
confidence: 99%
“…The genetic method, which consists in determining the deletion of 7 and/or 8 exons in the SMN1 gene, is the "gold standard" for diagnosis 13,20 . The deletions in the specified areas of the gene, in a patient in a homozygous state, confirm the diagnosis of SMA.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of protein is found in the motor neurons of the anterior horns of the spinal cord. SMN-protein of peripheral motor neurons has the following functions: participates in the process of mRNA; participates in the transport of mRNA in the axons of motor neurons; modulates the growth of axons and the dynamics of the cytoskeleton; SMN also plays an important role in maturation of axon terminals in muscles after childbirth; as a result of mutations in the SMN1 gene, peripheral motor neurons lose the ability to control the transition from preRNA to mRNA and produce the proteins necessary for their survival and functioning 8,12,13 .…”
Section: Introductionmentioning
confidence: 99%